Observation of plasma poloidal rotation in “Uragan-3M” torsatron from edge Hα fluctuation correlation studies - Konovalov, V.G.; Matsuoka, K.; Pavlichenko, O.S.; Shapoval, A.N.; Skibenko, A.I.; Suzuki, C. (Вопросы атомной науки и техники, 2002)
Studies of plasma edge Ha emission fluctuations firstly proposed for CHS heliotron/torsatron have been performed for RF produced/heated plasma in “Uragan-3M” torsatron. Approach is based on a realistic assumption that Ha emission fluctuations from plasma edge (ne≥10¹⁷m⁻³, Te≥10eV) defined mostly by electron density fluctuations. Having two Ha observation channels getting emission from plasma edge in 2 different poloidal locations of plasma one can study correlation of electron density fluctuations between these locations. Analysis of data included calculation of spectra of signals, their coherency and cross correlation between 2 signals for time windows 1 ms. Bands of rather high (>0.5) coherency were observed over the whole range (f<100 KHz) of frequencies. Calculation of cross correlation of digitally filtered (∆f=4 KHz) signals showed that time delay of low frequency part of signals coincides with time delay of no filtered signals and is decreasing with frequency increase. Conclusion of these observations is: time delay of low frequency part of signals reflects plasma poloidal rotation, time delay in the rest part of spectra reflects a dispersion properties of poloidally propagating density fluctuations.